Flame retardancy and mechanical properties of flax reinforced woven for composite applications. (March 2015) - Duquesne, Sophie; Samyn, Fabienne; Ouagne, Pierre; Bourbigot, Serge
This paper investigates the flame retardant and mechanical properties of a flax woven fabric that can be used to prepare biocomposites. The flame retardant properties of the fabric are first considered using different ammonium phosphate salts and intumescent systems. It is demonstrated that satisfactory performances can be achieved using this approach. Better performances were obtained with pure phosphate salts in comparison to intumescent systems. This was attributed first, to the carbonization effect of the flax that could thus react with the phosphate and/or its degradation products leading to a stabilisation of the system and second to the lower phosphorus content when the full intumescent system is considered. On the other hand, despite a loss of biaxial tensile properties, the ability of the fire retardant treated fabric to form complex shape such as a tetrahedron was successfully demonstrated. Finally, the flame retardant properties of one-ply composites, using a bio-based matrix (Bioplast from Biotec), was evaluated. It was shown that good fire retardancy performances could be achieved considering only the flame retardancy of the reinforcement phase. This approach has potential for developing future flame retarded biocomposites.